Evaluation of Sella Turcica Variations in Lateral Cephalometric Radiographs and its Association with Malocclusion - Taniya Poorsoleiman; Benyamin Kazemi; Maryam Tofangchiha; Mehdi Ranjbaran; Marjan Bolbolian; Francesco Pagnoni; Rodolfo Reda; Luca Testarelli (University of Zagreb. School of Dental Medicine, 2024)
Objectives: Understanding the shape and size of the sella turcica may help predict future orthodontic treatment needs related to skeletal malocclusion. This study aims to assess different morphological types of the sella turcica in lateral cephalometric radiographs and its correlation with malocclusion, as well as the relationship between gender and linear measurements of sella turcica. Materials and Methods: The lateral cephalometric radiographs of 410 volunteers (111 men and 299 women) aged 8 to 30 years were evaluated. The patients were divided into three groups based on their skeletal growth patterns (cl I, II, and III). Then the anatomical shape and linear dimensions of sella turcica were assessed. Measurements were made using Adobe Photoshop Version: 20.0.0 software, and data analysis was performed by IBM SPSS Statistics version 25. Results: The following morphologies were observed: normal (37.8%), oblique anterior wall (9.3%), double contour of the floor (21.5%), sella turcica bridge (8.8%), irregularity (notching) in the posterior part of sella turcica (16.6%), and pyramidal shape of the dorsum sellae (6.1%). No statistically significant relationship was found between sella turcica variations and skeletal malocclusion. The correlation between female sex with the diameter (p=0.027) and depth values (p=0.035) of sella turcica was statistically significant. There was no statistically significant difference (p>0.05) in length based on gender. Conclusion: The most morphological type reported was normal sella turcica (37.8%). Anatomical variations of sella turcica had no association with malocclusion. The most considerable depth and diameter of sella turcica were found in women.